2011
DOI: 10.1007/s13187-011-0212-4
|View full text |Cite
|
Sign up to set email alerts
|

East Meets West: A Brief Report of a Culturally Sensitive Breast Health Education Program for Chinese-Australian Women

Abstract: Chinese-Australian women are less likely to undergo breast health examination compared to women born in Australia, and cultural beliefs have been identified as a barrier to screening participation and breast health practices. We sought to promote awareness using trained lay health advisers (breast health advocates). This paper discusses the impact of the training program on advocate knowledge and beliefs, and women's experience as advocates. Thirty-seven of 50 women approached participated in an education prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…14 Past studies have also suggested that Asian survivors who have migrated to the Western world suffer from cultural barriers that lead to poorer outcomes in survivorship care. 15 This highlights the importance of taking into account cultural sensitivity when survivorship programs for Asian breast cancer survivors are designed.…”
Section: Discussionmentioning
confidence: 99%
“…14 Past studies have also suggested that Asian survivors who have migrated to the Western world suffer from cultural barriers that lead to poorer outcomes in survivorship care. 15 This highlights the importance of taking into account cultural sensitivity when survivorship programs for Asian breast cancer survivors are designed.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies show Chinese immigrants may face not only language barriers, but also cultural and other issues during the communication process (Jih et al, 2018;Kwok et al, 2011). Mixed methods research (MMR) which uses both quantitative and qualitative approaches to exam doctor-patient cancer communication might provide deepened and nuanced insights on some of the underlying reasons and barriers.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is possible that peer influence and support could be a far more useful tool than traditional health-promotion programs. One pointer to that are the positive results reported in studies which have used similar strategies among Chinese women living in Western countries (Crawford, Frisina, Hack, & Parascandalo, 2015;Kwok, Koo, D'Abrew, White, & Roylhouse, 2011;Maxwell et al, 2011).…”
Section: Discussionmentioning
confidence: 99%